2021
DOI: 10.1111/tbed.14062
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of SARS‐CoV‐2 and co‐infections in stray cats in Spain

Abstract: A new coronavirus known as SARS‐CoV‐2 emerged in Wuhan in 2019 and spread rapidly to the rest of the world causing the pandemic disease named coronavirus disease of 2019 (COVID‐19). Little information is known about the impact this virus can cause upon domestic and stray animals. The potential impact of SARS‐CoV‐2 has become of great interest in cats due to transmission among domestic cats and the severe phenotypes described recently in a domestic cat. In this context, there is a public health warning that nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 47 publications
8
69
0
1
Order By: Relevance
“…Experimental infections have shown that cats and, to a lesser extent, dogs are susceptible to SARS-CoV-2 and that cats can transmit the virus to other cats [18][19][20]. Infections in companion animals appear to have occurred as a result of human-toanimal transmission; however, the reported transmission of SARS-CoV-2 from farmed mink to in-contact humans, cats and dogs [21,22] and the detection of the virus in stray dogs and cats [23,24], suggest it is important to continue surveillance in companion animals. Here we conducted a survey of SARS-CoV-2 neutralising antibodies in cats and dogs attending UK veterinary practices.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental infections have shown that cats and, to a lesser extent, dogs are susceptible to SARS-CoV-2 and that cats can transmit the virus to other cats [18][19][20]. Infections in companion animals appear to have occurred as a result of human-toanimal transmission; however, the reported transmission of SARS-CoV-2 from farmed mink to in-contact humans, cats and dogs [21,22] and the detection of the virus in stray dogs and cats [23,24], suggest it is important to continue surveillance in companion animals. Here we conducted a survey of SARS-CoV-2 neutralising antibodies in cats and dogs attending UK veterinary practices.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SARS-CoV-2 titration and micro-neutralization assays are labor-intensive and expensive, requiring trained personnel with specific laboratory requirements such as culture areas and biosafety cabinets. ELISA techniques are widely used in this type of seroepidemiological survey performed in animals to detect the presence of anti-SARS-CoV-2 antibodies [2,3,14,24].…”
Section: Discussionmentioning
confidence: 99%
“…An in-house indirect ELISA was established for the detection of IgG specific for RBD of the spike protein [2,3]. Ninety-six-well plates were coated overnight, at 4 • C with 100 ng RBD protein in phosphate-buffered saline (PBS).…”
Section: Detection Of Sars-cov-2 Antibodies By In-house Elisamentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is almost no information on T. gondii in felids in BR1 (Sobrino et al, 2007), and no large-scale studies have been carried out to assess T. gondii distribution in these species in this area of the country. Because most of the sampling sites of the present study were located far from urban areas, feral and wild felines that (Sparkes et al, 2013)] has been shown to be high in mainland Spain, ranging between 12.3% and 52% (Millán et al, 2009;Villanueva-Saz et al, 2021). Although some studies have shown that seroprevalence to T. gondii in the endangered Iberian lynx (Lynx pardinus) is high in Spain, ranging between 44.0% and 81.5% (Roelke et al, 2008;Sobrino et al, 2007), its spatial distribution in south and central Spain could not have affected the high seroprevalence observed in wild ruminants in northern Spain.…”
Section: Discussionmentioning
confidence: 99%